Anticholinergic toxidromeofdatura toxicity: neostigmine reverses its toxicity - Mohamad, Nasir (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Datura belongs to ihe family of solanacae or"Kecubung" in Malaysia or"Trompetbloem" in Surinam. It is rich in alkaloids and terpenes and is often used for pulmonary conditions such as bronchial asthma. The seeds are ihe most toxic part of the plant as I 00 seeds contain ihe equivalence of approximately 6 mg of atropine. The main active chemicals present in datura are ihe tropane alkaloids scopolamine, atropine, and hyoscamine. Scopolamilie and atropine are anticholinergic deleriants. They block muscarinic receptors, which in turn excite dopaminergic neurons. They are readily absorbed, partially metabolized by ihe liver, and mostly eliminated in ihe urine, wiih a half-life of about four hours. We describe a case of acute datura ingestion in a 48 year-old gentleman presented to our emergency department after he allegedly consumed 4 fruits of datura. One hour after ingestion, he developed generalized muscle weakness associated wiih altered sensorium, his GCS was I 0115. On examination, he was found to be restless, dilated pupils of 4 mm in diameter. He was hyperihermic (T=38°C), tachycardic !HJR=lOO beats per minute), blood pressure of 130/80 mmHg, tachypnoiec (RIR=26), ~sence of neck stiffuess, dried and coated tongue and presence of urinary retention. In datura toxicity, life-ihreatening events require P.rompt supportive management The use of neostigmine as acetylcholinesterase inhibitor in an anti-cholinergic intoxication is reported to effectively reverse ihe effect of anti-cholinergic toxidrome. The doses and frequency of neostigmine administration can be titrated according to the clinical progress and improvement. Onr patient responded well to ihe regime given. Careful titration of ihe drug is required. Too high doses of neostigmine cause severe bradycardia, which may require intravenous atropine. In conclusion, early detection of toxicity (toxidrome) and a good history taking remain the most important elements in the diagnosis of datura toxicity in ihe Emergency Department. Delay in recognizing toxicity of datura may lead to serious morbidity and mortality.